Extrapulmonary complications of COVID-19 disease - Pecho-Silva, Samuel (2020)
SARS-CoV-2 infection is the most important emerging disease of this century. Since its inception to the present, it has caused almost a million deaths worldwide, becoming a real threat to public health. For this reason, new reviews and scientific studies in this regard are extremely important. In the same way, it is known that the main disease caused by this virus is confined to the respiratory system. However, there are still unknown aspects of the disease and within them are extrapulmonary complications. This review attempts to summarize all that is known at the time regarding the disease and its neurological, hematological, cardiological, kidney and liver complications.